First Large-Scale Eastern Mediterranean and Black Sea Stock Assessment Reveals a Dramatic Decline - Demirel, Nazli; Zengin, Mustafa; Ulman, Aylin (Frontiers in Marine Science, 2020)
The Mediterranean Sea is classified as a “data-poor” region in fisheries due to its low number of assessed stocks given its biodiversity and number of exploited species. In this study, the CMSY method was applied to assess the status and exploitation levels of 54 commercial fish and invertebrate stocks belonging to 34 species fished by Turkish fleets in the Eastern Mediterranean (Levantine) and Black Seas, by using catch data and resilience indices. Most of these marine taxa currently lack formal stock assessments. The CMSY method uses a surplus production model (SPM), based on official catch statistics and an abundance index derived from scientific surveys. The SPM estimates maximum sustainable yield (MSY), fishing mortality (F), biomass (B), fishing mortality to achieve sustainable catches (Fmsy), and the biomass to support sustainable catches (Bmsy). Our results show the estimated biomass values for 94% of the stocks were lower than the required amount to support sustainable fisheries (Bmsy). Of the 54 stocks, 85% of them can be deemed as overfished; two stocks were not subject to overfishing (Sardina pilchardus and Trachurus mediterraneus in the Marmara Sea) while only one stock (Sprattus sprattus in the Black Sea) is healthy and capable of producing MSY. Annual values of the stock status indicators, F/Fmsy and B/Bmsy, had opposing trends in all regions, suggesting higher stock biomasses could only be achieved if fishing mortality is drastically reduced. Recovery times and levels were then explored under four varying F/Fmsy scenarios. Under the best-case scenario (i.e., F = 0.5Fmsy), over 60% of the stocks could be rebuilt by 2032. By contrast, if normal fishing practices continue as usual, all stocks will soon be depleted [if not already] (F = 0.95Fmsy), whose recover may be impossible at later dates. The results of this study are supported by previous regional assessments confirming the overexploitation of Turkish fisheries is driving the near-total collapse of these marine wild fisheries. Hence, the need to urgently rebuild Turkey’s marine fisheries ought to be prioritized to ensure their future viability.